Comparative clinical evaluation of conventional nance appliance and modified aesthetic nance appliance (MANA) in maxillary premolar extraction cases: A prospective study - Shailesh Ram Kulkarni (Bioinformation, 2026)
Visible extraction spaces and aesthetic concerns during orthodontic treatment remain inadequately addressed by conventional anchorage appliances. Therefore, it is of interest to compare the Conventional Nance Appliance and Modified Aesthetic Nance Appliance (MANA) in 30 patients undergoing bilateral maxillary premolar extraction. Patients were allocated into two groups (n=15 each) and anchorage loss, space maintenance, soft tissue response, oral hygiene and patient satisfaction were assessed. MANA showed comparable anchorage control with significantly higher patient satisfaction and superior aesthetics. Thus, data show an aesthetic modification maintains clinical efficiency while improving patient-centered outcomes in orthodontic care.